The Effectiveness of Speedy English Grammar Application on Students’ Grammar Mastery in Simple Past Tense - Najilah, Ifa; Sudirman, Ade; Munawaroh, Tatu (Ma'soem University, 2024)
The objective of this research is to examine the effectiveness of Speedy Grammar application on students' grammar mastery in simple past tense at the twelfth grade of a vocational school in Banten. This research employed a quasi-experimental method with achievement tests in collecting the data. Achievement tests included pre-test and post-test. This research was conducted at the twelfth grade of a vocational school in Banten. The samples of this research were 40 students that consisted of 20 students of experimental and 20 students of control class. The experimental class used Speedy English Grammar and the control class used English Grammar and Test application. The data were analyzed by using statistical of program SPSS 22. Based on the result of data analysis, the result showed that mean of post-test both experimental and control class different are 76.70 and 70.45 and for the result of t-test obtained sign score 0.000 ? ? = 0.05. The result indicated the alternative hypothesis was accepted and the null hypothesis was rejected. It is concluded that Speedy English Grammar application was effective in improving students' grammar mastery in simple past test at the twelfth grade of a vocational school in Banten.